Developmental mitochondrial complex I activity determines lifespan. - Stefanatos, R.; Robertson, F.; Castejon-Vega, B.; Yu, Y.; Uribe, A.H.; Myers, K.; Kataura, T.; Korolchuk, V.I.; Maddocks, O.D.K.; Martins, L.M.; Sanz, A. (EMBO Reports, 2025)
Aberrant mitochondrial function has been associated with an increasingly large number of human disease states. Observations from in vivo models where mitochondrial function is altered suggest that maladaptations to mitochondrial dysfunction may underpin disease pathology. We hypothesized that the severity of this maladaptation could be shaped by the plasticity of the system when mitochondrial dysfunction manifests. To investigate this, we have used inducible fly models of mitochondrial complex I (CI) dysfunction to reduce mitochondrial function at two stages of the fly lifecycle, from early development and adult eclosion. Here, we show that in early life (developmental) mitochondrial dysfunction results in severe reductions in survival and stress resistance in adulthood, while flies where mitochondrial function is perturbed from adulthood, are long-lived and stress resistant despite having up to a 75% reduction in CI activity. After excluding developmental defects as a cause, we went on to molecularly characterize these two populations of mitochondrially compromised flies, short- and long-lived. We find that our short-lived flies have unique transcriptomic, proteomic and metabolomic responses, which overlap significantly in discrete models of CI dysfunction. Our data demonstrate that early mitochondrial dysfunction via CI depletion elicits a maladaptive response, which severely reduces survival, while CI depletion from adulthood is insufficient to reduce survival and stress resistance.